Physical activity and mental health in school-aged children: a prospective two-wave study during the easing of the COVID-19 restrictions - Philipp M. Kopp; Eva Möhler; Peter Gröpel (BMC, 2024)
Abstract Background Because physical activity (PA) has many benefits for children's and adolescents' mental health, it has been suggested that PA may be an effective strategy to physically and mentally recover from the COVID-19 pandemic. This study tested the reciprocal relationship between PA and mental health during the easing of COVID-19 restrictions. It was hypothesized that mental health during the pandemic would determine how much children and adolescents re-engage in PA after easing the restrictions. Furthermore, it was hypothesized that PA engagement would predict mental health improvement after the pandemic. Methods This was a prospective study with two measurement occasions. Pretest data collection was undertaken in February 2022, shortly before German authorities eased and lifted the COVID-19 restrictions. The follow-up (posttest) occurred six weeks later (April 2022). Both times, a sample of elementary and grammar school students aged 6 to 18 years (N = 170) reported their mental health problems and health-related quality of life. Mental health problems were assessed with the Strengths and Difficulties Questionnaire and health-related quality of life was assessed with the KIDSCREEN-52 questionnaire. PA was measured continuously during the study period using smart electronic devices with a built-in pedometer. Results PA gradually increased after the easing of COVID-19 restrictions (p < .001). This increase was unrelated to pretest mental health problems and health-related quality of life except for emotional symptoms (p = .041). Participants with higher emotional symptoms showed a sharper increase in PA towards the end of the study period. Furthermore, hyperactivity decreased (p = .004) and physical well-being (p = .004), perceived autonomy (p < .001), and perceived quality of school environment (p = .008) improved from before to after the easing of restrictions, yet participants' PA predicted none of these changes. Conclusions The adverse effects of COVID-19 containment on PA seem to alleviate after children and adolescents are allowed to return to schools. This is likely to be due to the school setting, which provides many different opportunities for formal and informal PA rather than students' mental health. School-related PA programs should be part of children's and adolescents' recovery from the pandemic .